Sarcopenia and Chronic Complications of Type 2 Diabetes Mellitus (The Review of Diabetic Studies, 2022)
Sarcopenia, defined as the loss of skeletal muscle mass and strength and/or a decrease in physical performance, is classically related to aging. However, chronic disease, including type 2 diabetes mellitus (T2DM), may accelerate the development of sarcopenia. Previous studies found strong association between T2DM and sarcopenia. Insulin resistance that exists in T2DM is thought to be the key mediator for impaired physical function and mobility which may lead to sarcopenia. T2DM may cause sarcopenia through the mediation of insulin resistance, inflammation, accumulation of advanced glycation end-products, and oxidative stress that may affect muscle mass and strength, protein metabolism, and vascular and mitochondrial dysfunction. On the other hand, loss of muscle in sarcopenia may play a role in the development of T2DM through the decreased production of myokines that play a role in glucose and fat metabolism. This review highlights the findings of existing literature on the relationship between T2DM and sarcopenia which emphasize the pathophysiology, chronic vascular complications, and the course of macrovascular and microvascular complications in T2DM.